Stem cells and genetic diseases - Shahid, S.; Irshad, S. (Вiopolymers and Cell, 2012)
In this review, we have discussed a role of stem cells in the treatment of genetic diseases including cochlear and retinal regeneration. The most perceptive use of stem cells at the genetic diseases is cellular repair of tissues affected by a genetic mutation when stem cells without such mutation are transplanted to restore normal tissue function. Keywords: stem cell, genetic disease, cochlea, retina, regeneration.